Pengaruh Pendidikan Agama Islam Terhadap Sikap Sosial Siswa di SMKN 1 Padang Gelugur Kabupaten Pasaman - Elsa Tiara Ningsih; Afrinaldi Afrinaldi; Wedra Aprison; Nurhasnah Nurhasnah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research is motivated by students who have a poor social attitude, this illustrates the gap between Islamic Religious Education and the Social Attitude of Students, this gap occurs because students do not understand good behavior in accordance with the teachings of Islam. To find out whether there is an influence of Islamic religious education on the social attitudes of students at SMKN 1 Padang Gelugur. To find out how much influence Islamic religious education has on the social attitudes of students at SMKN 1 Padang Gelugur The research method used is regression research with a quantitative approach, Data collection using questionnaires to 38 eleventh grade students who are active at SMKN 1 Padang Gelugur. The data processing techniques used are Validity Test, Reliability Test, Normality Test, Linearity Test, Simple Linear Regression Test, F Test and, Determinant Coefficient Test (R2). Based on data processing, the significance value (Sig) of 0.030 is smaller than <0.05, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of Islamic Religious Education (X) on the Social Attitude (Y) of SMKN 1 Padang Gelugur students. Then from the Determination Coefficient test, it is known that the influence of Islamic religious education (Independent Variable) on Social Attitude (Dependent Variable) is 12.4%.